Hydrological Characteristics of Kaligarang Watershed - Soewarno, Soewarno; Yuningsih, Srimulat (Forum Geografi, 2000)
This paper is a result of research concerning hydrological characteristic in the Garang Catchment Area. At present tha catchment area is often facing the problem of flooding in the dense populated area with cause a lot of loos in Semarang City. This research is aimed at studying hydrological harateristic in the Garang Catchment Area. Hydrological data are obtain from direct measurement at the stream gauging stations in the Garang Catchment Area and collected from Balai Hidrologi Office at Pusat Litbang Teknologi Sumber Daya Air in Bandung and from Hydrological Unit of Central Java Province. From this research were known the rainfall depth, their distribution and their return period; runoff coefficient; streamflow volume; dependable flow; flood discharge characteristi; and minimum discharge. From the some occuring flood indicates of the runoff coefficient is about 0.70. The water volume wasted to the sea is about 195 million m3/year. Yearly average of the dependable flow at stream gaunging stations: Garang â PajanganÂ is about 2.28 m3/sec; Garang â Patemon is about 0.92 m3/sec and Kreo â Pancur is about 1.26 m3/sec. Yearly mean of annual flood discharge at Garang â Pajangan is about 435 m3/sec. The maximum capacity of river channel is about 485 m3/sec. The flood discharge characteristic are as follows: time of travel of flood is generally one km/hour approximately, rising time is about 3 hours and time of recession is about 6 â 11 hours. The floods, they are generally occur at the night. Flush flood of 1022 m3/sec occured on January 26, 1990 is estimated on 50 year return period, with 15 year return period of rainfall. The range of minimum discharge is about 0.43 â 3.15 m3/sec. The maximum discharge is about 47.2 â 1118 times of the minimum discharge. Design of the dam in Kreo River at Jatibarang and Kripik River at Mundingan, also increasing of the reforestation area in the upstream catchment are an alternative to reduce the Garang River peak flood.